The nature of formative physical activities and sports in the development of senior volleyball players - Coutinho, P.; Ramos, A.; Fonseca, A. M.; Davids, K.; Mesquita, I. (International Journal of Sports Science & Coaching, 2021)
This study characterized developmental sporting activities undertaken by volleyball players between ages of 6 to 12 years. Highly skilled (n = 30) and less skilled (n = 30) players participated in retrospective interviews to identify the nature of their formative enrichment experiences (formal adult-led and informal child-led activities) and types of sports practised (team or individual sports). All participants reported involvement in multiple formal sport activities and informal child-led activities, confirming that they did not specialize early in volleyball. Highly skilled male players reported being involved in more formal, adult-led activities, generally, and more formal team sports. In contrast, highly skilled and less skilled female players participated in equal amounts of formal adult-led and informal child-led activities. Results partially supported the value of an early diversified sport involvement to develop functional behavioural adaptability needed to specialise later in sports like volleyball. Findings highlighted the importance of considering the nature and types of early enriching play and practice activities to better understand possible complementary transfer of training effects during specialization. Data also emphasized relevance of considering sex differences in future analyses of player developmental pathways.